EXPLORING MIDDLE SCHOOL STUDENT RESPONSE AND ATTITUDES TOWARD STEM ON HEAT AND TEMPERATURE TOPIC - Lola Jovita; Nurul Fitriyah Sulaeman; Shelly Efwinda (ISER (Indonesian Science Education Research), 2022)
This study explores the effect of STEM (Science, Technology, Engineering, and Mathematics) learning using the EDP (Engineering Design Process) model on the attitudes of seventh-grade junior high school students on heat and temperature. This research is quantitative. The method used in this study is a quasi-experimental study with a one-shot case study design. The sample is 31 students from class VII-11 Public Junior High School at Samarinda City. Data collection techniques using a questionnaire technique. The results of the data analysis of the value of R square, the coefficient of determination is 39,6%, and the significant value in the simple linear regression test is 0,000. These results indicate that STEM learning with the EDP model affects student attitudes, so applying STEM to shape students' attitudes towards STEM is essential.